Antimicrobial Resistance Pattern of Klebsiella pneumoniae Isolated from UTI Cases in and Around South Trivandrum District, Kerala, India - Suresh Babu (American Journal of Laboratory Medicine, 2026)
Background and objectives: Antimicrobial resistance among bacterial strains is an emerging problem. Urinary tract infections are one of the most common bacterial infections in humans, both in the hospital and the community settings. Multidrug resistance is seen in Klebsiella which serves as the most common cause of increased morbidity and mortality. The objective of this study was to isolate and evaluate the antimicrobial resistance pattern of Klebsiella pneumoniae from UTI cases in and around southern part of Trivandrum district, Kerala. Materials and Methods: This retrospective work was carried out between December 2024 and September 2025, at the Microbiology diagnostic laboratory, Dr. SM CSI Medical College and Hospital, Karakonam, Trivandrum district, Kerala. 200 cases of Klebsiella pneumoniae culture positive cases of UTI from both inpatients and outpatients were included in the study. Midstream and catheterized urine were collected with proper precautions, as per their clinical conditions. The isolates were obtained by culturing the samples in conventional media and identified as per CLSI guidelines. Antibiotic susceptibility of each of the isolate was performed in Mueller Hinton agar by disc diffusion test and interpreted as per CLSI standards. For quality control, Klebsiella pneumoniae ATCC 13883 strain was utilized. The collected data was entered in MS-Excel and statistical analysis was done using SPSS 17 software and were expressed as percentages. Results: Out of the 200 Klebsiella pneumoniae culture positive cases, >70 age group predominated (26.5%). Nearly two third of the cases were male. 62% of the cases were inpatients. Among the 124 inpatients, female medical ward cases predominated (41.9%) over other wards. There were 54 MDR Klebsiella pneumoniae positive cases, of the total 200 positive cases (27%), under study. Overall, 100% of the Klebsiella pneumoniae isolates were susceptible to the lifesaving drugs like, Colistin and Tigecycline, followed by Meropenem (75%), Cefoperazone/sulbactam (66.5%), Amikacin (63.5%) and Piperacillin/tazobactam (62%), in that order. Conclusion: Our study revealed emergence of MDR Klebsiella pneumoniae among UTI cases, evident by the finding of 27% of the isolates being resistant to all antibiotics used, except, Colistin and Tigecycline. Another important observation was the emergence of gentamicin, being a first line drug, as a more effective drug than the higher antibiotics, against some of the resistant strains isolated (58%).